Pilot Implementation of Human-Centered Model in Disaster Management: A Report From Landslides Area in Semarang City - Thomas Triadi Putranto; Novie Susanto (Indonesian Journal of Geography, 2017)
Semarang has a high potential of landslides occurrences in its almost area that should be noted by the stakeholders. Consider this fact, human as the part of the system should be used as a center of the disaster management system to reduce the risk caused by the disaster. An adapted model of human factor toolkits is developed to represent a specific phase of human-centered disaster management. This model presents four phases including major disaster scenario, human error analysis, safety critical task and performance influence factors (PIFs). As the preliminary implementation, this study takes the pilot implementation of each phase of the model to examine the reliability of the concept in the landslide cases, especially in Semarang city. The result shows that there is quite a high deviation between expected and observed behavior of the community and the government institution regarding the awareness states of the system.